Ideology Behind Implicature Meaning of Gus Dur’s Humor to Social, Political and Religious Critics - M. Yunal Sholahudz Dzihni; Ismatul Khasanah; Dian Putu Danayanti Degeng (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
This research investigates implicature on Gus Dur’s humor about social, political, and religion condition in Indonesia. This research was aimed to analyze implicature, especially focus on flouting maxim and the ideology of Gus Dur. This research used qualitative approach. Research design of this research is Critical Discourse Analysis (CDA). This research used Fairclough’s three models of CDA, those are textual analysis, discursive practice and social practice. The result showed that all types of floating maxim were found in Gus Dur’s humor speech about social, political and religious in Indonesia, those are floating maxim of quantity, quality, relevance and manner. Gus Dur expressed his critics through humor to show his concern about the social, political, and religion condition of indonesia. It showed that Gus Dur intended to show his critics by humor to create condition more relax and all of this formed by their family, social, and education environment that forms his idelogy.IntisariPenelitian ini menyelidiki implikatur pada humor Gus Dur tentang kondisi sosial, politik, dan agama di Indonesia. Penelitian ini bertujuan untuk menganalisis implikasi, terutama berfokus pada ideologi Gus Dur dibalik pelanggaran maxim. Penelitian ini menggunakan pendekatan kualitatif. Desain penelitian dari penelitian ini adalah Analisis Wacana Kritis (CDA). Penelitian ini menggunakan tiga model CDA dari Fairclough, yaitu analisis tekstual, praktik diskursif, dan praktik sosial. Hasil penelitian menunjukkan bahwa semua jenis pelanggaran maxim ditemukan dalam humor Gus Dur tentang sosial, politik dan agama di Indonesia, yaitu pelanggaran maxim kuantitas, kualitas, relevansi dan cara (manner). Gus Dur mengungkapkan kritiknya melalui humor untuk menunjukkan kepeduliannya tentang kondisi sosial, politik, dan agama di Indonesia. Itu menunjukkan bahwa Gus Dur bermaksud menunjukkan pada kritiknya dengan humor untuk menciptakan kondisi yang lebih santai dan semua itu dibentuk oleh lingkungan keluarga, sosial, dan pendidikan dan membentuk ideology dari Gus Dur.